Mitotic Phosphorylation Prevents the Binding of HMGN Proteins to Chromatin - Prymakowska-Bosak, Marta (American Society for Microbiology, 2001)
Condensation of the chromatin fiber and transcriptional inhibition during mitosis is associated with the redistribution of many DNA- and chromatin-binding proteins, including members of the high-mobility-group N (HMGN) family. Here we study the mechanism governing the organization of HMGN proteins in mitosis. Using site-specific antibodies and quantitative gel analysis with proteins extracted from synchronized HeLa cells, we demonstrate that, during mitosis, the conserved serine residues in the nucleosomal binding domain (NBD) of this protein family are highly and specifically phosphorylated. Nucleosome mobility shift assays with both in vitro-phosphorylated proteins and with point mutants bearing negative charges in the NBD demonstrate that the negative charge abolishes the ability of the proteins to bind to nucleosomes. Fluorescence loss of photobleaching demonstrates that, in living cells, the negative charge in the NBD increases the intranuclear mobility of the protein and significantly decreases the relative time that it is bound to chromatin. Expression of wild-type and mutant proteins in HmgN1(−/−) cells indicates that the negatively charged protein is not bound to chromosomes. We conclude that during mitosis the NBD of HMGN proteins is highly phosphorylated and that this modification regulates the interaction of the proteins with chromatin.